Chemical constituents of rennelua elliptica: the Malaysian ginseng / Nor Hadiani Ismail, Rohaya Ahmad and Faridahanim Mohd Jaafar - Ismail, Nor Hadiani; Ahmad, Rohaya; Mohd Jaafar, Faridahanim (Research Management Institute (RMI), 2011)
Rennellia ellitpica Korth. is a tropical shrub that can be found in lowland tropical rainforest in Malaysia. It is locally known as 'segemuk' and dubbed as Malaysia Ginseng due to the resemblance between roots of R. elliptica and roots of ginseng, as well as its many traditional uses. The decoction of the roots of this plant is traditionally used as treatment of body aches, as afterbirth tonic and also being claimed as aphrodisiac. The dried roots of R. elliptica that were previously collected from Taman Negara Kuala Keniam, Pahang were successively extracted using hexane, dichloromethane and methanol. The dichloromethane extract were absorbed onto acid washed silica (previously shaken with 4% oxalic acid, filtered and activated at 89 °C) and introduced to acid washed silica gel bed (60 cm X 5 cm) eluted with series of solvents, comprising of various compositions of hexanedichloromethane and dichloromethane-methanol in increasing polarity. Further isolation and purification utilizing various chromatographic procedures followed by careful analysis of spectral data including MS, IR, UV, 1D and 2D NMR as well as x-ray crystallography lead to identification of one new anthraquinone, 1,2-dimethoxy-6-methyl-9,10-anthraquinone (1) along with ten known anthraquinones namely nordamnacanthal (2), 2-formyl-3-hydroxy-9.10- anthraquinone (3), damnacanthal (4), 1-hydroxy-2-methoxy-6-methyl-9,10-anthraquinone (5), lucidin-cj-methyl ether (6), 3-hydroxy-2-methyl-9,10-anthraquinone (7), rubiadin (8), 2- hydroxy-3-methoxy-6-methyl-9,10-anthraquinone (9), rubiadin-1-methyl ether (10) and 3- hydroxy-2-hydroxymethyl-9,10-anthraquinone (11). The dichloromethane crude extract and the anthraquinones were screened for antiplasmodial activity in vitro. The dichloromethane extract inhibited the Plasmodium falciparum growth in vitro with IC50 value of 4.04 (jg/ml while most of anthraquinones tested were active inhibitors and the strongest inhibitor was shown by 3-hydroxy-2-methyl-9,10-anthraquinone with IC500.34|jM. The new anthraquinone, 1,2-dimethoxy-6-methyl-9,10-anthraquinone is an active inhibitor with IC50 value of 1.10 |jM.